Dynamic Cr(III) uptake by Macrocystis pyrifera and Undaria pinnatifida biomasses - Plaza Cazón, Josefina del Carmen (2013)
The increased industrial activity has resulted in the discharge of large amount of pollutants including non-degradable metals into the environment. Chromium is produced in several industrial processes and it can be found in the environment in two stable oxidation states, Cr(VI) and Cr(III). Cr(VI) is more hazardous due to its carcinogenic and mutagenic effects on living organisms. Although much less toxic, Cr(III) can also exert genotoxic effects under prolonged or severe exposure. It can be separated from the solution by precipitation but biosorption using brown algae seems to be an effective and sustainable treatment technique owing to its cost-effectiveness and environmental friendly characteristics. Macrocystis pyrifera and Undaria pinnatifida are two marine brown macroalgae with high capability of removing heavy metals including Cr(III) in batch mode of operation. In this work packed bed biosorption of Cr(III) by M. pyrifera and U. pinnatifida biomasses was evaluated.